Availability and Characteristics of Hemp-Derived Psychoactive Cannabis Products: A Pilot Study in Cleveland, Ohio - Jessica Suratkal; Erika Trapl; Catherine Osborn; Pranav Vasu; Stephanie Pike Moore (Ohio Journal of Public Health, 2024)
Background: Hemp-derived psychoactive cannabis products (HDPCPs), such as delta-8 tetrahydrocannabinol (THC), emerged onto the market as an alternative to cannabis following the 2018 US Farm Bill which legalized hemp. Research on HDPCPs remains limited. The purpose of this research was to evaluate the availability, placement, and consumption modality of HDPCPs as well as to identify potential defining characteristics of consumers. Methods: Between October 2022 and January 2023, researchers visited a random sample of 82 tobacco retailers in Cleveland, Ohio, to evaluate the availability of HDPCPs marketed as delta THC (eg, delta-8 or delta-10). Information was captured on where the HDPCPs were placed (eg, behind the counter, on the counter, by candy, or elsewhere) as well as the consumption modality (eg, edible or inhaled). Among retailers who stocked these products, clerks were asked who typically buys these products and how often they are purchased. Results: Over two-fifths (41.5%) of retailers carried HDPCPs. Most retailers (97.1%) carried delta THC products behind the counter and carried products as inhaled (82.4%), edible (70.6%). More than half of retailers (55.9%) carried both inhaled and edible forms of HDPCP. Retail clerks reported on a range of ages of consumers from younger to older or “everyone.” Conclusion: Hemp-derived psychoactive cannabis products are prevalent in this pilot study sample. These findings necessitate additional research to better quantify the population health impact of these products to determine if regulatory action may be necessary to protect public health.
Keywords: Hemp-derived psychoactive cannabis products; Delta-8; Market research; Substance use